PM21-particle stimulation augmented with cytokines enhances NK cell expansion and confers memory-like characteristics with enhanced survival - Oyer, Jeremiah L.; Croom-Perez, Tayler J.; Hasan, Md Faqrul; Rivera-Huertas, Javier A.; Gitto, Sarah B.; Mucha, Joanna M.; Zhu, Xiang; Altomare, Deborah A.; Igarashi, Robert Y.; Copik, Alicja J. (Frontiers in Immunology, 2024)
NK cell therapeutics have gained significant attention as a potential cancer treatment. Towards therapeutic use, NK cells need to be activated and expanded to attain high potency and large quantities for an effective dosage. This is typically done by ex vivo stimulation with cytokines to enhance functionality or expansion for 10-14 days to increase both their activity and quantity. Attaining a robust methodology to produce large doses of potent NK cells for an off-the-shelf product is highly desirable. Notably, past reports have shown that stimulating NK cells with IL-12, IL-15, and IL-18 endows them with memory-like properties, better anti-tumor activity, and persistence. While this approach produces NK cells with clinically favorable characteristics supported by encouraging early results for the treatment of hematological malignancies, its limited scalability, variability in initial doses, and the necessity for patient-specific production hinder its broader application. In this study, stimulation of NK cells with PM21-particles derived from K562-41BBL-mbIL21 cells was combined with memory-like induction using cytokines IL-12, IL-15, and IL-18 to produce NK cells with enhanced anti-tumor function. The use of cytokines combined with PM21-particles (cytokine and particle, CAP) significantly enhanced NK cell expansion, achieving a remarkable 8,200-fold in 14 days. Mechanistically, this significant improvement over expansion with PM21-particle alone was due to the upregulation of receptors for key stimulating ligands (4-1BB, IL-2, IL21R), resulting in a synergy that drives substantial NK cell growth, showcasing the potential for more effective therapeutic applications. The therapeutic potential of CAP-NK cells was demonstrated by the enhanced metabolic fitness, persistence, and anti-tumor function both in vitro and in vivo. Finally, CAP-NK cells were amenable to current technologies used in developing therapeutic NK cell products, including CRISPR/Cas9based techniques to generate a triple-gene knockout. Taken together, these data demonstrate that the Internal addition of cytokines enhanced the already effective method of ex vivo generation of therapeutic NK cells with PM21-particles, yielding a superior NK cell product for manufacturing efficiency and potential therapeutic applications.